Clinical researchThe ERCC2 K751 polymorphism is associated with breast cancer risk - Hosseini, Mojgan; Houshmand, Massoud; Ebrahimi, Ahmad (Archives of Medical Science, 2009)
Introduction: Numerous studies are addressing associations of polymorphisms in DNA repair genes and cancer risks, because accurate and efficient DNA repair is crucial to genomic integrity and fidelity. ERCC2 are important in DNA nucleotide excision repair and lie on chromosome 19q13.3. We genotyped constitutive variants ERCC2 K751Q and R156R in approximately 400 adults with breast adenocarcinoma and 160 controls of Iranian women. Material and methods: Totally 560 Iranian sporadic breast cancer affected women compare to control group were studied by PCR-RFLP for ERCC2 (K751Q and R156R). Results: Our results showed that heterozygote genotype ERCC2 (751) has the highest frequency in both groups (21.8 in patients and 8.7 in control group). The genotype ERCC2 (751) GT were most risk factor in our population [GG/TT odds ratio, 5.90 (95% confidence interval, CI 11.45-12.15) p = 0.001, GG/GT odds ratio, 4.737 (95% CI, 9.03-9.92) p = 0.029, TT/GT odds ratio, 5.465 (95% CI, 10.41-11.45) p = 0.002]. Conclusions: We conclude that not only G/G and T/T in our patients was not associated with breast cancer risk but also there is a relation between presence of G/T and increasing of breast cancer risk.